2014
DOI: 10.1016/j.soilbio.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of soil properties of shooting fields to lead biovailability and toxicity to Enchytraeus crypticus

Abstract: a b s t r a c tVariation in soil properties may cause substantial differences in metal bioavailability and toxicity to soil organisms. In this study, lead bioavailability and toxicity to Enchytraeus crypticus was assessed after 21 days exposure to soils from different landscapes of a shooting range containing 47e2398 mg Pb/kg dry weight (dw). Soils had different pH CaCl2 (3.2e6.8) and organic matter contents (3.8e13% OM), therefore artificial soils with different pH and OM contents and two natural reference so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
18
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 43 publications
(66 reference statements)
7
18
3
Order By: Relevance
“…Luo et al [5] found that internal Pb concentrations in E. crypticus ranged from 10.4 to 776 mg Pb/kg dry body weight, with total Pb concentrations from 15 to 656 mg Pb/kg dry soil in soils from a shooting range. Santorufo et al [23] reported 17.3 mg to 300 mg Pb/kg dry body wt in E. crypticus exposed to urban soils, with total lead concentrations from 18.7 mg to 695 mg Pb/kg dry soil.…”
Section: Lead Bioaccumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al [5] found that internal Pb concentrations in E. crypticus ranged from 10.4 to 776 mg Pb/kg dry body weight, with total Pb concentrations from 15 to 656 mg Pb/kg dry soil in soils from a shooting range. Santorufo et al [23] reported 17.3 mg to 300 mg Pb/kg dry body wt in E. crypticus exposed to urban soils, with total lead concentrations from 18.7 mg to 695 mg Pb/kg dry soil.…”
Section: Lead Bioaccumulationmentioning
confidence: 99%
“…Earthworm survival has been reported to be very tolerant to lead, whereas reproduction was more sensitive [3]. The reproduction of the species Enchytraeus crypticus showed similar sensitivity to lead in field-contaminated soils from a shooting range [5]. The reproduction of the species Enchytraeus crypticus showed similar sensitivity to lead in field-contaminated soils from a shooting range [5].…”
Section: Introductionmentioning
confidence: 97%
“…This study is part of a broader investigation that aimed at assessing the ecotoxicological risk of Pb in shooting range soils and deals with the effects on springtails; earlier studies described the effects on earthworms and enchytraeids [17,18]. Six natural field soils were collected from different landscapes (bullet plot, forest and grass lands) of a shooting field in the Netherlands, representing a gradient of Pb pollution but also different pH and organic matter contents.…”
Section: Introductionmentioning
confidence: 99%
“…While the reason for the difference is not clear (Chelinho et al, 2011), other authors have demonstrated a correlation with these variables, especially for pH, conductivity, clay and sand content, and the carbon/nitrogen ratio (Chelinho et al, 2011;Luo et al, 2014;Vašíčková et al, 2015). Any lack of correlation observed might be because the selected organism can effectively survive and reproduce within the range of conditions found in the sampled points; in this case, pH values fell between 4.3-8.2, organic content measured at 1.2-42%, and clay concentrations were between 1-29% (Table 1) Soil parameters accounted for 38.0% of the overall variability.…”
Section: /9mentioning
confidence: 93%
“…The observed differences in vegetation cover result from the different effects that soil properties exert on living organisms (Luo et al, 2014). In secondary forests, organic matter content showed little effect when compared with those of other factors; for example, humidity and pH heavily influenced the Poduromorpha and Symphyla groups.…”
Section: /9mentioning
confidence: 99%